Effect of UPVC Waste Additive on Water-Immersion Durability of AC-WC Asphalt Mixtures - Ifan Adi Saputra; Anwar Efendy; Adryan Fitrayudha; Nurul Hidayati (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Water-induced deterioration remains one of the major causes of premature failure in Asphalt Concrete–Wearing Course (AC-WC) pavements, reducing pavement service life and increasing maintenance costs. This study investigates the effect of incorporating Unplasticized Polyvinyl Chloride (UPVC) waste as an additive on the durability of AC-WC mixtures subjected to different water immersion durations. Marshall testing was conducted following the 2018 Bina Marga General Specifications (Revision 2) using specimens immersed for 0.5, 1, 2, 4, 24, and 48 hours. The evaluated parameters included Marshall stability, flow, Marshall Quotient (MQ), Void in Mix (VIM), Void in Mineral Aggregate (VMA), Void Filled with Bitumen (VFB), and retained durability. The results indicate that the mixture containing 6% UPVC maintained satisfactory performance after prolonged immersion. Marshall stability remained above the minimum specification, decreasing from its optimum value to 1249 kg after 48 hours, while durability remained at 114.9%, exceeding the required 90%. However, the flow value gradually increased to 4.67 mm, indicating reduced resistance to permanent deformation under extended immersion. These findings demonstrate that incorporating 6% UPVC enhances the moisture resistance of AC-WC mixtures while supporting the sustainable utilization of plastic waste in pavement engineering.